Digital Platform Potential for Asnaf Zakat Entrepreneurs: A Systematic Literature Review - Meerangani, Khairul Azhar; Abdul Hamid, Mohammad Fahmi; Hashim, Siti Nurul Izza; Jofri, Muhamad Hanif; Mansor, Muhamad Sayuti (HMARS, 2023)
The implementation of the asnaf entrepreneurial transformation model through the Human Development Program is a proactive initiative of the State Islamic Religious Council (MAIN) aimed at increasing the asnaf group's potential in the entrepreneurial field. This initiative is in line with the goal of MAIN to increase the effectiveness of zakat distribution through a twopronged strategy to ensure that every asnaf can live a prosperous life while expanding their potential to break free from the shackles of poverty. The Industrial Revolution 4.0 has contributed to the rapid development of information and communication technology. The development of various online applications and social media platforms has had a positive impact on people's lives. Therefore, enterprises and entrepreneurial activities, especially the small and medium-sized enterprise (SME) sector, need to enhance their respective competitiveness by participating in digital entrepreneurship platforms. Therefore, this study aims to determine the potential of digital platforms to increase the competitiveness of asnaf zakat entrepreneurs. The study was conducted qualitatively using a descriptive approach through a systematic analysis of highlights. The main sources for this study were obtained from online databases, namely Scopus and Web of Science. The data were then analyzed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The results of the study suggest that digital platforms have the potential to increase the competitiveness of asnaf zakat entrepreneurs through six approaches, namely resources, personality, opportunities, networking, environment, and knowledge. Therefore, the study can serve as a guide for the State Islamic Religious Council to develop appropriate programs and approaches to improve literacy and participation of asnaf zakat entrepreneurs in the digital platform.